Residents' social capital in rural tourism development: Guanxi in housing demolition. (December 2021) - Dai, Meiling; Fan, Daisy X.F.; Wang, Rong; Ou, Yanghong; Ma, Xiaolong
Abstract: Social capital plays an essential role in the early stage of rural tourism development. Taking the family as the research unit, this study applied social capital theory to examine how guanxi serves residents' interests in negotiations during housing demolition. Nonparticipant observations and in-depth interviews were conducted to identify the utility and essence of guanxi during housing demolition for rural tourism development in a Chinese village. The results show that guanxi, as a kind of social capital, plays an important role in rural tourism development, and that the internal mechanism through which guanxi exerts its utility is ' guanxi - power - interest.' The study offers important theoretical and practical implications for both governments and tourism developers which benefits the destination management. Highlights: This study explores the role of guanxi during housing demolition in rural tourism. Nonparticipant observations and in-depth interviews were used. Money-grabber and intellectual-centered interest groups were formed through guanxi. The impact of social capital is functionalised in the guanxi -power-interest mechanism.